Georgia : Adjusting in the Face of Uncertainty - World Bank (Washington, DC, 2014)
Economic growth picked up in the final quarter of 2013 as policy uncertainty was reduced, confidence strengthened, and budget execution substantially increased. Surge in spending in the last quarter of the year partially offset sluggish outlays earlier to leave the fiscal deficit for 2013 as a whole at 2.6 percent of gross domestic product (GDP), a marginal improvement from 2012. There was a substantial increase in spending in the fourth quarter, although annual expenditures continued to be 8 percent below the budgeted amount. Revenue collections were also low due to subdued economic activity. Although the fiscal deficit is expected to increase to 3.8 percent of GDP in 2014, it should decline thereafter given the government's commitment to fiscal consolidation. The current account deficit narrowed in 2013 as exports picked up, especially to Russia and the Commonwealth of Independent States (CIS), while imports languished due to weak investment and consumption. The unemployment problem persisted with a net decline in business sector jobs by 5 percent during the first three quarters of 2013. In this context, the report presents political developments; recent economic developments; and economic and structural policies.